Menstruation-Related Disorders—Dysmenorrhea and Heavy Bleeding—as Significant Epiphenomena in Women With Rheumatic Diseases - Orlandi, Martina; Vannuccini, Silvia; El Aoufy, Khadija; Melis, Maria Ramona; Lepri, Gemma; Sambataro, Gianluca; Bellando-Randone, Silvia; Guiducci, Serena; Cerinic, Marco Matucci; Petraglia, Felice (Frontiers in Pharmacology, 2022)
Background: In women with rheumatic diseases (RDs) menstruation-related disorders have never been investigated. The aim of this study was to evaluate gynecological symptoms/disorders in fertile age women with RDs. Materials and methods: All patients (n = 200) filled up a self-administered questionnaire on their gynecological history, menstrual cycle pattern, menstrual-related symptoms, and quality of life (QoL). The RD group was then compared to a control group of 305 age-matched fertile age women. Results: Among patients with RDs, 58% had arthritis, 40% connective tissue diseases (CTDs), and 1.5% systemic vasculitis. No differences were observed between CTDs and arthritis, except for a family history of HMB which was more common among women with CTDs (p < .01). When compared to controls, women with RDs reported more frequent heavy menstrual bleeding (HMB) during adolescence (51.7 and 25.4%, respectively; p = .0001) and adult life (37.7 and 25.9%, respectively; p = .0065). Also, dysmenorrhea in adolescence was significantly more common among cases (55.6 and 45.4%, respectively; p = .0338). Gynecological pain (dysmenorrhea, non-menstrual pelvic pain, dyspareunia, dysuria, and dyschezia) in patients with RDs was more frequent than in controls (p = .0001, .0001, .0001, .0001, .0002, respectively). Considering women who reported moderate and severe symptoms in RDs, dysmenorrhea and dyspareunia remain significantly more frequent in women with RDs than in controls (p = .0001; p = .0022; respectively). QoL scores were significantly reduced in women with RDs, either in physical (p = .0001) and mental domains (p = .0014) of short-form 12. Conclusion: Women affected by RDs frequently presented menstruation-related disorders; thus, female patients with RDs should be questioned about gynecological symptoms and referred to the gynecologist for an accurate evaluation.